Temporal regulation of the generation of neuronal diversity in Drosophila. - Yasugi, T.; Nishimura, T. (Development, Growth and Differentiation, 2016)
For the construction of complex neural networks, the generation of neurons and glia must be tightly regulated both spatially and temporally. One of the major issues in neural development is the generation of a large variety of neurons and glia over time from a relatively small number of neural stem cells. In Drosophila, neural stem cells, called neuroblasts (NBs), have been used as a useful model system to uncover the molecular and cellular machinery involved in the establishment of neural diversity. NBs divide asymmetrically and produce another self-renewing progenitor cell and a differentiating cell. NBs are subdivided into several types based on their location in the central nervous system. Each type of NB has specific features related to the timing of cell generation, cell cycle progression, temporal patterning for neuronal specification, and termination mechanism. In this review, we focus on the molecular mechanisms that regulate the proliferation of NBs and generate a large variety of neuronal and glia subtypes during development.